RESERVOIR CHARACTERIZATION AND HYDROCARBON RESOURCE ESTIMATION IN THE MIDDLE ARANG X INTERVAL, FOXTROT FIELD, WEST NATUNA BASIN - Harsa Pratama, Nalendra
The Indonesian government plans to increase oil and gas production to reach the target of 1 million BOPD and 12 BSCFD with the aim of transitioning energy to new, renewable energy (Ministry of Energy and Mineral Resources, 2022). One of the oil and gas producing fields is the Foxtrot Field which is located in Anambas Islands Regency, Riau Islands. Geologically, this field is located in the West Natuna Basin and has several reservoir targets, one of which is located in the Arang Formation. Further research must be carried out in order to determine the characteristics, quality and quantity of the reservoir in the Arang Formation, precisely in the Middle Arang X interval